Bellini Duct Carcinoma Misdiagnosed with Urothelial Papillary Carcinoma. (10th February 2020) - El Khoury, Joey; Abdessater, Maher; Halabi, Rami; Nasr, Fadi; Boustany, Johnny; Kanbar, Anthony; El Hachem, Charbel; El Khoury, Raghid
Abstract : Background . Collecting (Bellini) duct carcinoma (CDC) or Bellini duct carcinoma (BDC) is a rare subtype of kidney tumors, accounting for less than 3% and known to have the worst prognosis. It is known to have multiple clinical presentations; this is why it can be easily misdiagnosed. The aim of this article is to present a case of CDC that was initially misdiagnosed with urothelial papillary carcinoma (UPC) in a 41-year-old male. Case Presentation . Our patient presented with a left flank pain evolving for one month and one episode of gross macroscopic hematuria. Upon presentation, he had left costovertebral angle tenderness. Initial lab tests were normal. Computed tomography revealed a 5 cm solid mass of the left renal pelvis and multiple infracentimetric perihilar lymph nodes. Subsequently, the patient had left nephroureterectomy. Microscopic examination showed the presence of a high-grade urothelial papillary carcinoma of the renal pelvis' lumen. All four of the dissected lymph nodes showed disease metastasis. Three years after establishing the diagnosis, the patient presented again for chronic abdominal pain, with a recent history of weight loss. CT scan showed a left paraaortic mass infiltrating the left psoas muscle over a length of 12 cm. Immunohistochemical profiling of this mass confirmed the diagnosis of Bellini duct carcinoma, rejecting the initial diagnosis of UPC. Therefore, the patient required a cisplatin-gemcitabine-based chemotherapy regimen. Conclusion . BDC remains one of the rare aggressive subtypes of RCC, having a multitude of initial clinical presentations and an unfavorable prognosis. In this patient, CDC was masquerading as a transitional cell carcinoma that should always be kept in mind as a possible presentation. Corresponding early imaging and histopathology exams are primordial for a correct diagnosis and thus a better prognosis.